Chemical Constituents of Cycas sancti-lasallei - Vincent Antonio S. Ng, Esperanza Maribel G. Agoo, Chien-Chang Shen, Consolacion Y. Ragasa (Journal of Applied Pharmaceutical Science, 2015)
Chemical investigation of the dichloromethane extracts of Cycas sancti-lasallei, a plant endemic to the Philippines, led to the isolation of squalene (1), β-sitosterol (2a), stigmasterol (2b), and triglycerides (3) from the sarcotesta; 2a, 2b, 3,and phytyl fatty acid esters (4) from the endotesta; 2a, 2b, 3,and β-sitosteryl fatty acid esters (5) from the sclerotesta; and 3 and 5 from the bark. The structures of 1-5 were identified by comparison of their 1H NMR and/or 13C NMR data with those reported in the literature.
Keywords: Cycas sancti-lasallei, Cycadaceae, squalene, beta-sitosterol, stigmasterol, triglycerides, phytyl fatty acid esters.